1997
DOI: 10.1038/sj.bjp.0701089
|View full text |Cite
|
Sign up to set email alerts
|

Reduced responsiveness of rat mesenteric resistance artery smooth muscle to phenylephrine and calcium following myocardial infarction

Abstract: 1 We evaluated responses of peripheral resistance arterial smooth muscle to a 1 -adrenoceptor stimulation in a rat model of heart failure in relation to neurohumoral changes, wall structure, receptor density and cellular calcium handling. 2 Plasma samples and third order mesenteric artery side-branches were obtained from Wistar rats after induction of left ventricular infarction (MI) or sham surgery. Vessels were denuded of endothelium, sympathectomized, depleted of neuropeptides, and mounted in a myograph for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Although we did not evaluate the neurohumoral activation, the InfHF rats presented hyporeactivity to the ␣-agonist phenylephrine. In contrast with a down-regulation of ␣-adrenoceptors found in rat mesenteric arteries after MI, Feng et al (1996) and Stassen et al (1997b) found no changes in the density of ␣ 1 -adrenoceptors in those vascular beds that displayed a decreased responsiveness to phenylephrine. However, absence of changes in the density of ␣ 1 -adrenoceptors does not rule out changes in the receptor signaling pathway that may lead to a reduction in responsiveness.…”
Section: Discussionmentioning
confidence: 55%
“…Although we did not evaluate the neurohumoral activation, the InfHF rats presented hyporeactivity to the ␣-agonist phenylephrine. In contrast with a down-regulation of ␣-adrenoceptors found in rat mesenteric arteries after MI, Feng et al (1996) and Stassen et al (1997b) found no changes in the density of ␣ 1 -adrenoceptors in those vascular beds that displayed a decreased responsiveness to phenylephrine. However, absence of changes in the density of ␣ 1 -adrenoceptors does not rule out changes in the receptor signaling pathway that may lead to a reduction in responsiveness.…”
Section: Discussionmentioning
confidence: 55%
“…Arteries of increasing branching order were made to contract with phenylephrine. This agonist activates α 1 ‐adrenoceptors that are expressed by ASM cells (Stassen et al. , 1997) but do not directly stimulate calcium influx in endothelial cells (Dora et al.…”
Section: Discussionmentioning
confidence: 99%
“…Arteries of increasing branching order were made to contract with phenylephrine. This agonist activates a1-adrenoceptors that are expressed by ASM cells (Stassen et al, 1997) but do not directly stimulate calcium influx in endothelial cells (Dora et al, 2000). Because it can be debated whether the endothelium of small arteries and arterioles expresses a1-adrenoceptors (Tuttle and Falcone, 2001), additional smooth muscle stimuli were also used.…”
Section: Rhp Hilgers and Jgr De Meymentioning
confidence: 99%
“…NE content of the extract was measured by high-performance liquid chromatography and fluorescent detection, 19 after which the tissues were solubilized in 1N KOH (24 hours, room temperature) and DNA content was determined. 20 Unlike for NE, the levels of dopamine and epinephrine were below detection limits in the embryonic arteries and heart.…”
Section: Ne and Dna Contentmentioning
confidence: 99%